1987
DOI: 10.1002/pen.760271310
|View full text |Cite
|
Sign up to set email alerts
|

On the crystallinity and some structure/property relationships of poly(ethylene terephthalate)—poly(amide‐6,6) blends

Abstract: Following the ester‐amide interchange reaction in the poly(ethylene terephthalate)/poly(amide‐6, 6) (PET/PA) system in the presence of p‐toluenesulfonic acid (TsOH), samples were injection molded and tested in the tensile mode. A brittle fracture was observed for these unoriented specimens. To separate the influence of the crystallinity from that of the interphases, the samples were studied using differential scanning calorimetry (DSC). The DSC results indicated an increase of crystallinity in the blends cause… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0

Year Published

1992
1992
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(26 citation statements)
references
References 12 publications
0
26
0
Order By: Relevance
“…Reactively compatibilized melt blends of PLA have been studied with many different polymers [13,[31][32][33][34]. However, there are only few reports on polyamidepolyester blends utilizing a catalyst [35][36][37][38][39] (and none on PLA-PA11) to enhance interchange reactions. Titanium alkoxides are widely reported as effective catalysts for interchange reactions [26,[40][41][42].…”
Section: Introductionmentioning
confidence: 99%
“…Reactively compatibilized melt blends of PLA have been studied with many different polymers [13,[31][32][33][34]. However, there are only few reports on polyamidepolyester blends utilizing a catalyst [35][36][37][38][39] (and none on PLA-PA11) to enhance interchange reactions. Titanium alkoxides are widely reported as effective catalysts for interchange reactions [26,[40][41][42].…”
Section: Introductionmentioning
confidence: 99%
“…Interchange reactions in PA/PET blends were promoted by the addition of a catalyst (26Ϫ29). The unoriented blends were brittle (26). The brittleness of reacted and unannealed blends (29) was attributed to the increase in the PET crystallinity induced by the presence of PA.…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that polyester–polyamide copolymers are formed through ester–amide interchange reaction in melt blending of PET and PA 16–18. Pillon et al19, 20 characterized the ester–amide interchange reaction of PET and PA catalyzed by p ‐toluenesulfonic acid by DSC, 1 H and 13 C NMR. Watanabe et al21 reported that PBT and PA 6 were an incompatible polymer pair.…”
Section: Introductionmentioning
confidence: 99%